Carbon fiber reinforced Zn–MnO2 structural composite batteries. (16th June 2021) - Chen, Junyan; Zhou, Yang; Islam, Mohammad S.; Cheng, Xinying; Brown, Sonya A.; Han, Zhaojun; Rider, Andrew N.; Wang, Chun H.
Abstract: Structural composite batteries, which can simultaneously carry mechanical loads and store electric energy, have the potential to significantly reduce the system weight of electric-powered systems including electric cars, unmanned air systems, and mobile robots. Recent research in this area has primarily focused on carbon-fiber based lithium-ion batteries, which require stringent protection against factors such as toxicity, moisture, and overheating, making it particularly challenging to realize the potential of structural batteries. Herein, we propose a novel carbon fiber reinforced Zn–MnO2 structural composite battery featuring a MnO2 cathode and a zinc ion anode; carbon fibers conduct current and provide stiffness and strength. The resulting structural Zn–MnO2 composite battery, which can be manufactured using a simple vacuum consolidation process, without the need for inert gloveboxes, demonstrates an excellent tensile strength of 293 MPa and a high specific capacity of 145.9 mAh g −1 . Moreover, the structural composite battery achieves an excellent energy density of 181.5 Wh kg −1 and retains 88.3% capacity after 100 cycles. The new carbon fiber Zn–MnO2 structural composite battery offers huge potential for next-generation energy-storing structures that are safe, eco-efficient, and provide multifunctional performance. Graphical abstract: Image 1